THE EFFECT OF POPULATION EXPLOSION ON FAMILY STANDARD OF LIVING IN CALABAR, NIGERIA - Michael, Inah, Grace; Usang, Inah, Egu; Chukwudi, Osuchukwu, Nelson; Etim, John; Onah, Ogri, Angela Imanso; Chukwudi, Osuchukwu, Easter (European Scientific Journal, ESJ, 2014)
A nation whose accurate and current population figure is uncertain cannot plan well. It is always threatening if a population keeps exploding without an observable increase in the resources available, and this has posed a serious challenge/worry to Calabarians and the world in general. This paper investigates the effects of population explosion on family standard of living in Calabar – Urban of Cross River State, Nigeria. The major objective of this paper is raising consciousness on the need to discuss population issues in order to proffer long lasting remedies to its effect on family standard of living, its management to guarantee economic sustainability, development and family wellbeing. The sources of data were primary and secondary. 102 semi – structured questionnaires were designed/administered, reviewed literature and interviews were used too. Data generated were analyzed using descriptive statistics such as mean, simple percentages and illustrative graphs. The findings show that the population of females (60.8%) doubles the male population (39.2%) in Calabar – Urban which could indirectly be attributed to the possibility of population explosion among other causes like illiteracy, poor family planning, poverty, religion and migration which is influenced by war, disaster, search for jobs/education, polygamy/early marriage and climate change. The study demonstrates: poor education, increased cost of living, increased crime rate, overcrowding, family stress, malnutrition, health complications, morbidity and mortality as effects of population explosion on families. This paper recommends that, there is need for mass education, equity in resources allocation to both rural/urban settings and encouraging agricultural practice with the aim of eradicating poverty and illiteracy which will in turn help in the control of population explosions in order to strike a balance with the available resources.